A numerical investigation of the linear hydrodynamic stability of Newtonian and weakly non-Newtonian channel flows as described by the Orr-Sommerfeld equation - Van der Fort, Zareer (Department of Mathematics and Applied Mathematics, 2014)
Includes abstract.